Modeling Ai-Generated Misinformation: Shariah, Ethical And Forensic Perspectives From Malaysia - Hadi Akbar Dahlan; Hadi Affendy Dahlan; Nur Khalidah Dahlan (Universiti Sains Islam Malaysia, 2026)
Non-Indexed Publication